A COMPLETE NMR STUDY OF DOXAZOSIN CHARACTERIZATION - Itamar Luís Gonçalves; Mariana Maier Gaelzer; Gabriel Oliveira de Azambuja; Christianne Gazzana Salbego; Vera Lucia Eifler-Lima (Drug Analytical Research, 2017)
Doxazosin is an important drug used for treating hypertension and prostatic hyperplasia. An enantiomeric mixture (R)/(S) doxazosin mesylate was complete characterized by NMR and additionally FT-IR spectroscopy techniques. Were performed different NMR experiments, such as APT, HSQC, and HMBC in order to confirm the NMR signals assignments. All the hydrogens and the most of carbons atoms were assigned.